Long non-coding RNAs in cutaneous squamous cell carcinoma - Saarelainen, Inka (My University, 2026)
Cutaneous squamous cell carcinoma (cSCC) is a keratinocyte-derived malignancy, and its most significant risk factor is chronic and cumulative exposure to solar ultraviolet (UV) radiation. cSCC represents the most common metastatic skin cancer, and advanced or metastatic disease is associated with a markedly poor prognosis. The aim of this study was to identify novel and specific therapeutic targets as well as potential biomarkers to inhibit tumor growth and dissemination and to improve the clinical management of cSCC. Long non-coding RNAs (lncRNAs) have been shown to play a central role in the pathogenesis and in the regulation of tumor growth and dissemination of cSCC. LINC01558 has previously been reported to encode lncRNA that associates with a complex referred to as the invasion cluster 1. In this study, we analyzed the role of LINC01558 expressed in cSCC cells in regulating cell growth, viability, migration and invasion. In addition, the modulation of key signaling pathways was assessed following gene silencing. The effects of LINC01558 were investigated in primary cSCC cell lines UT-SCC-12A and UT-SCC-118, as well as metastatic cell lines UT-SCC-59A and UT-SCC-115. LINC01558 appears to regulate key signaling pathways, including AKT1 and P38 by reducing their activity. LINC01558 also regulates ERK1/2 signaling molecules by reducing both their activity and total protein levels, which indicate that LINC01558 regulates these signaling molecules transcription, translation or protein stability, rather than just the activation. Functional analyses reveal that silencing of LINC01558 suppresses growth and viability and significantly inhibits migration and invasion potentially via AKT1, P38 and ERK1/2 signaling molecules, indicating its contribution of tumor aggressiveness. Collectively, these results suggest that LINC01558 represents as a potential biomarker and therapeutic target in cSCC, though further studies are needed to determine its clinical relevance.
Keywords: cancer; skin cancer; cutaneous squamous cell carcinoma; keratinocyte; long non-coding RNA